2015
DOI: 10.1158/1055-9965.epi-15-0237
|View full text |Cite
|
Sign up to set email alerts
|

Leisure-Time Spent Sitting and Site-Specific Cancer Incidence in a Large U.S. Cohort

Abstract: Background: Time spent sitting is distinctly different from accumulating too little physical activity and may have independent deleterious effects. Few studies have examined the association between sitting time and site-specific cancer incidence.Methods: Among 69,260 men and 77,462 women who were cancer-free and enrolled in the American Cancer Society Cancer Prevention Study II Nutrition Cohort, 18,555 men and 12,236 women were diagnosed with cancer between 1992 and 2009. Extended Cox proportional hazards regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 48 publications
2
41
1
Order By: Relevance
“…This null relationship is similar to that reported by Patel and colleagues in the American Cancer Society’s Cancer Prevention Study-II Nutrition Cohort (Patel et al, 2015). Authors found that among men and women, sitting ≥6 hrs/day compared to <3 hrs/day during leisure time was not associated with colorectal cancer risk.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This null relationship is similar to that reported by Patel and colleagues in the American Cancer Society’s Cancer Prevention Study-II Nutrition Cohort (Patel et al, 2015). Authors found that among men and women, sitting ≥6 hrs/day compared to <3 hrs/day during leisure time was not associated with colorectal cancer risk.…”
Section: Discussionsupporting
confidence: 88%
“…To our knowledge, this is the first report of a potential interactive effect of physical activity and sedentary time on colorectal cancer risk. There is some evidence of an interactive effect from a study of total cancers, in which the adverse effect of sitting time on overall cancer risk varied by background level of physical activity (Patel et al, 2015). The notion that the protective effects of physical activity on cancer risk may be stronger among subgroups defined by sedentary activity is not without cause.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reductions in sedentary behavior are recommended for cancer reduction and improvement in overall mortality [54]. In fact, in a recent large U.S. cancer prevention cohort study led by the American Cancer Society, even after adjusting for physical activity and BMI, increased leisure-time spent sitting (≥6 hours) was associated with a higher risk of total cancer incidence in women, not men, and specifically with multiple myeloma, breast and ovarian cancers [55]. Sedentary behavior is becoming even more commonplace in our modern society, where less physical activity is required and increased sitting is the norm.…”
Section: Introductionmentioning
confidence: 99%
“…Another study focused solely on breast cancer and indicated that > 7-h walking per week reduced the risk for breast cancer by 14% [5]. Conversely, longer leisure time spent sitting was associated with a higher incidence of breast cancer, multiple myeloma and ovarian cancer in women [6]. However, the biochemical changes that underlie these beneficial effects on the incidence of various cancer types are not fully understood.…”
Section: Introductionmentioning
confidence: 99%